The perspectives and the challenges of Paediatric Radiology: An interview with Dr Georgia Papaioannou, Head of the Paediatric Radiology Department at the ‘Mitera’ Children's Hospital in Athens, Greece - Mammas, Ioannis N. (Exp Ther Med, 2019)
Dr Georgia Papaioannou, MD, PhD, Head of the Paediatric Radiology Department at ‘Mitera’ Children's Hospital in Athens (Greece), is one of the most talented Paediatric Radiologists in Greece. She graduated from the Medical School of Athens of the National and Kapodistrian University of Athens in 1996 and she was trained in Radiology at the 2nd Department of Radiology of the Medical School of Athens and in Paediatric Radiology in Great Ormond Street Hospital for Children (GOSH) in London (UK). Her special interests focus on foetal magnetic resonance imaging (MRI) and special applications of paediatric MRI, such as MR enterography and MR urography. According to Dr Papaioannou, medical education in Paediatric Radiology has to be of excellent quality, raising professional career and academic opportunities. Paediatric Radiology focuses on the diagnostic imaging of foetuses, neonates, infants, children and adolescents and represents the oldest subspecialty of Radiology. The advent in technology and computer science, which is strongly associated with Radiology, has launched a new era for Paediatric Radiology training and practice. Digital imaging and archiving, telemedicine, fused imaging, evolution of sonographic equipment, computed tomography (CT) and MRI scanners have opened new horizons to the understating of paediatric physiology and pathophysiology and have contributed significantly in precision Medicine and the implication of targeted therapies into clinical practice. Modern paediatric imaging focuses on radiation protection issues and launches faster sequences in all modalities, in order to reduce the number and duration of sedation. The diagnosis of neonatal and paediatric viral infections is routinely clinical and laboratory; however, Paediatric Radiology assists the diagnostic approach by excluding other entities, if that is required, i.e., in complex cases or hospitalized children, and mainly by revealing associated complications.